CATALYTIC PERFORMANCE OF ZSM-5 ZEOLITE IN HEAVY HYDROCARBON CATALYTIC CRACKING: A REVIEW - Ratu Ulfiati (Scientific Contributions Oil and Gas, 2019)
Low quality heavy oils and residues, which are subsequently obtained by processing heavy crudes, are considered as alternate suitable source for transportation fuels, energy and petrochemicals. ZSM-5 zeolite with high Si/Al ratio and modified with phosphorous and La has showed not only high selectivity to light olefins but also high hydrothermal stability for the steam catalytic cracking of naphtha. Kaolin is promising natural resource as raw material to synthesis of ZSM-5 zeolite. The utilization of acid catalysts with large pore size or hierarchically structured and high hydrothermal stability to resist the severity of the steam catalytic cracking (or thermal and catalytic cracking) operation conditions to maximize the olefin production.